Orality, Electronic Judicial Expedient and videoconference: The role of the Civil High Courts in the quarantine’s times and the COVID-19 outbreak - Alegre Valdivia, Judith (2020)
The conception of the Civil High Court has changed since the COVID-19 pandemic outbreak. This approach represents the new vision of the jurisdictional labor. The globalization process and the recent rules derived from the «Consejo Ejecutivo del Poder Judicial» have had created a new form of the legal practice in the High Courts. This change enforced diversity values, for example: the celerity process, the person’s right to defense and the due legal process.